Збереженість біологічної цінності компонентів заморожених ягідних сумішей за тривалого низькотемпературного зберігання - Григоренко, Олена Віталіївна; Григоренко, Елена Витальевна; Hryhorenko, Olena; Загорко, Надія Петрівна; Загорко, Надежда Петровна; Zahorko, Nadiia (My University, 2019)
UK: У статті досліджено збереженість біологічно цінних речовин у компонентах заморожених ягідних сумішей за тривалого низькотемпературного зберігання. Показано, що ягоди аґрусу та йошти добре зберігають споживчі властивості та біологічну цінність при заморожуванні та можуть бути рекомендовані для заморожування розсипом і складання заморожених сумішей, як нетрадиційні види сировини. RU: В статье исследована сохранность биологически ценных веществ в компонентах замороженных ягодных смесей при длительном низкотемпературном хранении. Показано, что ягоды крыжовника и йошты хорошо сохраняют потребительские свойства и биологическую ценность при замораживании и могут быть рекомендованы для замораживания россыпью, а также составления замороженных смесей, как нетрадиционные виды сырья. EN: The purpose of our research was to develop an optimal composition of frozen berry mixes and to study the change in the quality of components during long frozen storage. It is established that as a result of freezing and long frozen storage there are changes in the nutritional and biological value of berries due to changes in the chemical composition depending on species characteristics. Frozen berries of all species are well preserved in shape, consistency, natural color, sometimes acquired even better flavoring qualities (reduction of nausea and taste abrasion). The value of the sugar index in frozen berries decreased in comparison with the initial by 2-6%. In gooseberries this indicator has increased significantly (from 9 to 10), the taste of berries has become more harmonious. Deep freezing of berries provides a sufficiently high content of ascorbic acid (24.7-202.0 mg / 100 g) with long-term preservation, and after 9 months of frozen storage amounted to 78% in gooseberries and 84% in yoshta (Interspecific hybrid of blackcurrant and gooseberry). Regarding the content of flavonoids, their conservation at the end of storage in all kinds of berries was high enough - 83-88%, which correlated with the preservation of bright color of berries. Pectic substances are best preserved in the gooseberries, yoshta and blackcurrant (94-96% of the original content). More significant losses of pectin substances in samples of red current and raspberry (13 and 10%) caused a noticeably softening of the consistency of these berries and the selection of juice during defrosting. The results of the conducted research allow to recommend the investigated varieties of gooseberries and yoshta for the freezing by spreading, as well as for the production of quick-frozen fruit and berry mixtures.
Сохраняемость биологической ценности компонентов замороженных ягодных смесей при длительном низкотемпературном хранении
Biological value preservation of frozen berry mixtures components at long-term low-temperature storage
Keywords: ягоди; заморожування; низькотемпературне зберігання; біологічна цінність